The microclimate of maize and bean crops in tropical America: a comparison between monocultures and polycultures planted at high and low density - Castro León, Vilma (1991)
This study characterizes the microclimates of maize and bean crops planted in monocultures and polycultures at two planting densities in Costa Rica. The hypothesis that the density and mixture of plants affects the microclimate within a field is evaluated as part of a larger study to identify environmental factors relevant tp the spread of disease by insects in tropical agricultural systems. In general, the results support the dindings of many previous studies that the density and morphological characteristics of the plants strongly influence the microclimate within an agricultural fiels. This research differed from most agricultural microclimate studies in that fields planted at two densities with different mixtures of plants were observed concurrently in tropical America.